Islamic Principles in Marketing: An Overview of Islamic Marketing mix in Social-Media Campaign - Syafril, Syafwendi; Hadziq, M. Fuad (LPPM Universitas Terbuka, 2021)
The increasing number of internet users among Muslims worldwide has open opportunities for business players to develop Islamic marketing and get attention from them. Social media becomes a popular platform for the Muslim community to interact, communicate, and share regarding humanity, education, donation, and the Islamic lifestyle. This paper arranges to analyzes the Islamic marketing mix that must be existed in social media campaigns. The Islamic principles in marketing are the main key to determine whether businesses not only provide sharia-compliant products and services but also succeed to comminates it based on Islamic ethics and value. The library research was conducted in research methodology to review marketing theory and concept from an Islamic perspective. Findings. The analytical result shows that the integrated Islamic principles such as halalan tayyiban, anti-monopoly, gharar, speculation, excessive action, manipulative sales tactic, etc., should be eliminated in the marketing mix in social media campaigns. All that aims to ensure marketing activities run properly according to Shariah principles.